Resilience among adult survivors of childhood neglect: A missing piece in the resilience literature. (July 2017) - Ben-David, Vered; Jonson-Reid, Melissa
Abstract: Despite the established long-term effect of childhood maltreatment, some proportion of adult individuals, who suffered childhood maltreatment, appear more resilient than others and continue to function well in life. We searched the databases of MEDLINE, PsycINFO and ERIC in order to identify relevant studies on resilience among adult survivors of child neglect, which constitutes the most common form of child maltreatment. We found that the vast majority of quantitative ( n = 41) and qualitative ( n = 45) studies on resilience among adult survivors focused on survivors of sexual and physical abuse rather than neglect. Only few studies examined neglect often along with other forms of child maltreatment. We reviewed the studies, identified gaps in the existing literature, and suggested directions for future research. Highlights: Few studies have examined resilience in adult survivors of neglect. Resilience was measured as successful functioning or absence of negative factors. The proportion of resilient survivors of maltreatment was relatively small. Resiliency prior to age 18 was strongly associated with continued resiliency. Positive relationships, coping skills and optimism were protective factors.